2004
DOI: 10.11646/zootaxa.744.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Description of two new species of the catfish genus Trichomycterus from southeastern Brazil (Siluriformes: Trichomycteridae)

Abstract: Two new species of Trichomycterus from isolated small river basins of southeastern Brazil are described: T. pantherinus, new species, from the Rio Santa Maria da Vitória basin, and T. caudofasciatus, new species, from the Rio Itabapoana basin. Both new species are diagnosed by a combination of morphological features, also occurring in T. alternatus and T. longibarbatus, including number of pectoral-fin rays, odontodes and branchiostegal rays, long filamentous first pectoral-fin ray and wide opercular patch of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…Species of the T. nigroauratus group have been reported to be associated with the bottom leaf-litter [32,69], and most species of the T. nigricans group are commonly found below large rocks during day light [74], but T. santaeritae, a species of the T. nigricans group, highly differs by having lighter coloration (i.e., light yellow with dark brown spots), is diurnal and psammophilic [36]. Similarly, field studies have indicated different habitats preferences for species of Psammocambeva, with many having diurnal habits [13,35,75] and some others nocturnal [76]. Most species of this clade have been found associated with gravel substrate [35,75], but some species such as T. auroguttatus are highly associated to sandy bottom [13], exhibiting a relatively large eye that is slightly dorsally protruded (Figure 6B).…”
Section: Morphological Diversity Of Osteological Structuresmentioning
confidence: 99%
“…Species of the T. nigroauratus group have been reported to be associated with the bottom leaf-litter [32,69], and most species of the T. nigricans group are commonly found below large rocks during day light [74], but T. santaeritae, a species of the T. nigricans group, highly differs by having lighter coloration (i.e., light yellow with dark brown spots), is diurnal and psammophilic [36]. Similarly, field studies have indicated different habitats preferences for species of Psammocambeva, with many having diurnal habits [13,35,75] and some others nocturnal [76]. Most species of this clade have been found associated with gravel substrate [35,75], but some species such as T. auroguttatus are highly associated to sandy bottom [13], exhibiting a relatively large eye that is slightly dorsally protruded (Figure 6B).…”
Section: Morphological Diversity Of Osteological Structuresmentioning
confidence: 99%
“…Colour patterns prove to be an efficient characteristic to distinguish many species in Trichomycterinae (Alencar & Costa, ; ; Bockmann et al ., ; Bockmann & Sazima, ; Castellanos‐Morales, ; Lima & Costa, ; Wosiacki, ; ; Wosiacki & de Pinna, ; ), but it is highly variable for some species, as with C. davisi (Nascimento et al ., ) and for C. iheringi (da Silva et al ., ). An important morphological characteristic in the distinction of C. horacioi refers to the colouration pattern formed by circular scattered dark blotches slightly variable in size in the inner skin layer and small black spots on outer skin layer.…”
Section: Discussionmentioning
confidence: 99%
“…Trichomycterus Valenciennes comprises small catfishes, usually about 50-150 mm SL, inhabiting mountain rivers of South America and southern Central America. Each species often is restricted to a short section of a river drainage (Eigenmann, 1918;Costa, 1992; Barbosa & Costa, 2003;Alencar & Costa, 2004;Lima & Costa, 2004). Although known to contain many species, Trichomycterus is poorly known (de Pinna, 1998) with many of the known species based on brief descriptions and many others undescribed (e. g., Barbosa & Costa, 2003;Alencar & Costa, 2004;Bockmann & Sazima, 2004;Lima & Costa, 2004).…”
Section: Introductionmentioning
confidence: 99%